2021
DOI: 10.1038/s42005-021-00728-8
|View full text |Cite
|
Sign up to set email alerts
|

Experimental demonstration of coherence flow in PT- and anti-PT-symmetric systems

Abstract: Non-Hermitian parity-time ($${{{{{{{\mathcal{P}}}}}}}}{{{{{{{\mathcal{T}}}}}}}}$$ P T ) and anti-parity-time ($${{{{{{{\mathcal{APT}}}}}}}}$$ APT )-symmetric systems exhibit novel quantum properties and have attracted increasing interest. Although many counterintuitive phenomena in $${{{{{{{\mathcal{P}}}}}}}}{{{{{{{\mathcal{T}}}}}}}}$$ P T - and $${{{{{{{\mathcal{APT}}}}}}}}… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 56 publications
1
13
0
Order By: Relevance
“…8 where (a), (b) and (c) depict the dynamics of various types of quantum coherences in the unbroken phase and (d), (e) and (f) depict the dynamics of various types of quantum coherence in the broken phase. Similar patterns of coherence dynamics are observed as in the case of the optics setup [24]. Our results in Fig.…”
Section: Experimental Demonstration Of the Dynamics Of Quantum Cohere...supporting
confidence: 89%
See 2 more Smart Citations
“…8 where (a), (b) and (c) depict the dynamics of various types of quantum coherences in the unbroken phase and (d), (e) and (f) depict the dynamics of various types of quantum coherence in the broken phase. Similar patterns of coherence dynamics are observed as in the case of the optics setup [24]. Our results in Fig.…”
Section: Experimental Demonstration Of the Dynamics Of Quantum Cohere...supporting
confidence: 89%
“…A single qubit coherence flow in PT-symmetric and anti-PT-symmetric systems was demonstrated experimentally using an optical setup and it was observed that coherence flow oscillates back and forth in the unbroken PT-symmetric and anti-PT-symmetric regimes while in broken phase, coherence flow attains a stable value in both PT-symmetric and anti-symmetric systems [24]. We investigated the dynamics of quantum coherence (total, local and global coherence) in the maximally entangled (Bell) state, when one qubit of the Bell state is acted upon by the PT-symmetric Hamiltonian at r = 0.6 (unbroken phase) and at r = 1.4 (broken phase).…”
Section: Experimental Demonstration Of the Dynamics Of Quantum Cohere...mentioning
confidence: 99%
See 1 more Smart Citation
“…Note that in the experiment, the constructed Hamiltonian is exactly (1), which is anti-PTsymmetric, there is no need to remove the iΓI term artificially as is done when simulating PT -symmetric systems [4][5][6]. Although H APT and H PT = ±iH APT have similar eigensystem structures, a recent work [25] suggests that they behave differently in the context of coherence flow between the system and environment. When taking the phonon degrees of freedom into account, evolutions under H APT might decohere more slowly than those under H PT , as studied in [27].…”
Section: Experimental Implementation and Verification Of The Anti-pt ...mentioning
confidence: 99%
“…The information and energy exchange between anti-PT -symmetric systems and environment are different from the PT -symmetric counterpart. These result in different information-exchange scheme, e.g., coherence flow [25], between anti-PTsymmetric systems and the PT -symmetric counterpart. Interestingly, recent theoretical works [26,27] studied the evolution of qubits under H APT when coupled to a bosonic bath, and claim that these qubits decohere more slowly compared to those under Hermitian or PTsymmetric Hamiltonians.…”
Section: Introductionmentioning
confidence: 99%